Strategia postępowania u młodych osób z nadciśnieniem tętniczym i innymi czynnikami ryzyka - Bryl, Wiesław (Przewodnik Lekarza/Guide for GPs, 2010)
In the following paperwork there have been showed the treatment rules of children and adolescents with hypertension and coexisting risk factors. The role and possibilities of nonpharmacological treatment have been discussed, mainly in the field of diet modification and physical activity promotion. The necessity of stable influencing on child and familiar environment have been stressed.